Catchment effects of a future Nordic bioeconomy: From land use to water resources - Eva Skarbøvik; Philip Jordan; Ahti Lepistö; Brian Kronvang; Marc I. Stutter; Jan E. Vermaat (Ambio, 2020)
In the future, the world is expected to rely increasingly on renewable biomass resources for food, fodder, fibre and fuel. The sustainability of this transition to bioeconomy for our water systems depends to a large extent on how we manage our land resources. Changes in land use together with climate change will affect water quantity and quality, which again will have implications for the ecosystem services provided by water resources. These are the main topics of this Ambio special issue on “Environmental effects of a green bio-economy”. This paper offers a summary of the eleven papers included in this issue and, at the same time, outlines an approach to quantify and mitigate the impacts of bioeconomy on water resources and their ecosystem services, with indications of useful tools and knowledge needs.

Nordic Bioeconomy Pathways: Future narratives for assessment of water-related ecosystem services in agricultural and forest management - Jelena Rakovic; Martyn N. Futter; Katarina Kyllmar; Katri Rankinen; Marc I. Stutter; Jan Vermaat; Dennis Collentine (Ambio, 2020)
Further development of the bioeconomy, the substitution of bioresources for fossil resources, will lead to an increased pressure on land and water resources in both agriculture and forestry. It is important to study whether resultant changes in land management may in turn lead to impairment of water services. This paper describes the Nordic Bioeconomy Pathways (NBPs), a set of regional sectoral storylines nested within the global Shared Socioeconomic Pathways (SSP) framework developed to provide the BIOWATER research program with land management scenarios for projecting future developments to explore possible conflicts between land management changes and the Water Framework Directive (WFD). The NBPs are a set of narrative storylines capturing a range of plausible future trajectories for the Nordic bioeconomy until 2050 and that are fit for use within hydrological catchment modelling, ecosystem service studies and stakeholder dialogue about possible changes in agricultural and forestry management practices.

Inter- and intra-species intercropping of barley cultivars and legume species, as affected by soil phosphorus availability - Tegan Darch; Courtney D. Giles; Martin S. A. Blackwell; Timothy S. George; Lawrie K. Brown; Daniel Menezes-Blackburn; Charles A. Shand; Marc I. Stutter; David G. Lumsdon; Malika M. Mezeli; Renate Wendler; Hao Zhang; et al. (Plant and Soil, 2018)

Does the combination of citrate and phytase exudation in Nicotiana tabacum promote the acquisition of endogenous soil organic phosphorus? - Courtney D. Giles; Timothy S. George; Lawrie K. Brown; Malika M. Mezeli; Alan E. Richardson; Charles A. Shand; Renate Wendler; Tegan Darch; Daniel Menezes-Blackburn; Patricia Cooper; Marc I. Stutter; David G. Lumsdon; et al. (Plant and Soil, 2017)

The mineralisation of dissolved organic matter recovered from temperate waterbodies during summer - Marc I. Stutter; Jonathan Cains (Aquatic Sciences, 2016)

The composition, leaching, and sorption behavior of some alternative sources of phosphorus for soils - Marc I. Stutter (Ambio, 2015)

Microbial biomass phosphorus contributions to phosphorus solubility in riparian vegetated buffer strip soils - William M. Roberts; Rachel A. Matthews; Martin S. A. Blackwell; Sabine Peukert; Adrian L. Collins; Marc I. Stutter; Philip M. Haygarth (Biology and Fertility of Soils, 2013)